A composite adsorbent for volatile organic compound adsorption and preparation method thereof

Through the synergistic effect of modified porous carbon and photocatalyst, a composite adsorbent was prepared, which solved the problems of poor adsorption effect of volatile organic matter and secondary pollution in the prior art, and achieved efficient, low-cost and environmentally friendly VOCs removal effect.

CN119158544BActive Publication Date: 2025-03-11DEZHOU GUANGYUAN ENVIRONMENTAL PROTECTION TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411648593.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-11
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

When adsorbing volatile organic compounds (VOCs), the adsorption effect is average, and there are problems of secondary pollution and high cost.

Method used

A composite adsorbent is prepared by synergistically acting with the photocatalyst. The method includes using cellulose as a carbon source, sulfur doping and modification treatment, combined with photocatalytic action of nanotitanium dioxide, to form a composite adsorbent with high adsorption capacity and green environmental protection characteristics.

Benefits of technology

The adsorption and removal efficiency of volatile organic matter is improved, the cost is reduced, secondary pollution is avoided, and the composite adsorbent is easy to recover.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of environmental pollution control, and discloses a composite adsorbent for volatile organic matter adsorption and a preparation method thereof. The composite adsorbent uses cellulose as a carbon source, uses 2-(chloromethyl)ethylene sulfide to modify the cellulose to obtain sulfur-containing cellulose, and carbonizes the cellulose under the action of potassium hydroxide, a porogen, to obtain sulfur-doped porous carbon. The sulfur-doped porous carbon is then modified by a mixed acid to obtain modified sulfur-doped porous carbon. Tetrabutyl titanate is used as a titanium source, and a hydrothermal reaction is performed to obtain the composite adsorbent. Nano titanium dioxide and the modified sulfur-doped porous carbon act synergistically, and the removal efficiency of volatile organic matter is further improved through adsorption and photocatalysis. The composite adsorbent is green and environmentally friendly, has low cost, is easy to recycle, and avoids secondary pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmental pollution control, and in particular to a composite adsorbent for adsorbing volatile organic matter and a preparation method thereof. Background Art

[0002] Volatile organic compounds (VOCs) are common air pollutants, referring to organic compounds with a saturated vapor pressure greater than 70Pa at room temperature and a boiling point within 260℃ at normal pressure, or all organic compounds with corresponding volatility and a vapor pressure greater than or equal to 10Pa at 20℃, mainly including hydrocarbons, aromatic hydrocarbons, ketones, acids, alcohols, lipids, amines and organic acids, etc. With the development of the economy and the progress of society, indoor air pollution caused by volatile organic compounds has attracted widespread attention. Most indoor volatile organic compounds are toxic and have serious impacts on human health and the ecological environment.

[0003] The main methods for treating volatile organic compounds include adsorption, condensation, combustion, biological and photocatalytic degradation, among which adsorption technology is one of the economical and effective methods for treating low-concentration volatile organic compounds. Chinese patent application CN108246259A discloses a method for preparing a biomass carbon material that efficiently adsorbs volatile organic compounds. The biomass waste is used as a raw material. After pretreatment, the biomass carbon material is prepared by carbonization and graphitization treatment technology under a protective atmosphere. The material has excellent adsorption performance and high adsorption capacity for volatile organic compounds in the atmosphere. However, a single biomass carbon material loses its adsorption capacity as time goes by during the adsorption process and reaches adsorption saturation. It will release the previously adsorbed harmful substances again, becoming a new source of pollution and causing secondary pollution. At the same time, its adsorption selectivity and recycling performance still need to be improved. Chinese patent application CN106422719A discloses an indoor volatile organic compound remover, which is mainly composed of the following raw materials: nano titanium dioxide, ultraviolet catalytic powder, visible light catalytic powder, dispersant, suspending agent, anionic surfactant, and polyphosphide. It can effectively and directly remove pollution sources by catalysis, decomposition, and polymerization, and can eliminate formaldehyde, toluene, xylene, ammonia, and volatile organic compounds in the air. However, the reaction rate of a single photocatalyst to remove volatile organic compounds is average and the cost is high. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In order to solve the above technical problems, the present invention provides a composite adsorbent for the adsorption of volatile organic compounds and a preparation method thereof. Through the synergistic effect of modified porous carbon and photocatalyst, the problem of the general adsorption and removal effect of the adsorbent on volatile organic compounds is solved, and it is green, environmentally friendly and low in cost.

[0006] (II) Technical solution

[0007] In order to achieve the above object, the present invention discloses a method for preparing a composite adsorbent for adsorbing volatile organic compounds, comprising the following steps:

[0008] Step 1, add cellulose and sodium hydroxide solution into reactor A, stir and mix evenly, then add 2-(chloromethyl)ethylene sulfide, stir and mix to react, after the reaction is completed, wash with acetone and deionized water, and dry at 60° C. for 12 hours to obtain sulfur-containing cellulose;

[0009] Step 2: Add sulfur-containing cellulose and potassium hydroxide to reactor B, grind them evenly, place them in a tube furnace, and carbonize them in an argon atmosphere. After carbonization, cool them, wash them with dilute hydrochloric acid and deionized water until they are neutral, and vacuum dry them at 60° C. for 12 h to obtain sulfur-doped porous carbon.

[0010] Step 3: Add deionized water, sulfuric acid solution and nitric acid solution into the reactor C, mix well, add sulfur-doped porous carbon, stir, react, filter after the reaction, wash with deionized water, and vacuum dry at 60° C. for 12 h to obtain modified sulfur-doped porous carbon;

[0011] Step 4: add ethanol solution, tetrabutyl titanate, hydrogen peroxide and modified sulfur-doped porous carbon to reactor D, mix evenly, add acetic acid to adjust the pH to 3-5, transfer to a polytetrafluoroethylene reactor, and undergo a hydrothermal reaction. After the reaction is completed, filter, wash with deionized water, and vacuum dry at 60°C for 12 hours to obtain a composite adsorbent.

[0012] Preferably, in step 1, the mass ratio of cellulose, sodium hydroxide solution and 2-(chloromethyl)ethylene sulfide is 100:(2800-3200):(155-215).

[0013] Preferably, the reaction temperature in step 1 is 25-35° C., and the reaction time is 36-48 h.

[0014] Preferably, the sodium hydroxide solution in step 1 is a sodium hydroxide aqueous solution with a mass concentration of 30%.

[0015] Preferably, in step 2, the mass ratio of sulfur-containing cellulose to potassium hydroxide is 100:(350-420).

[0016] Preferably, in step 2, the heating rate of carbonization is 2-4°C / min, the carbonization temperature is 650-700°C, and the carbonization time is 2-3h.

[0017] Preferably, in step three, the mass ratio of deionized water, nitric acid solution, sulfuric acid solution, and sulfur-doped porous carbon is (900-1200): (250-300): (320-380): 100.

[0018] Preferably, the reaction temperature in step 3 is 35-45° C., and the reaction time is 3-6 h.

[0019] Preferably, in step 4, the mass ratio of the ethanol solution, tetrabutyl titanate, hydrogen peroxide and modified sulfur-doped porous carbon is (1800-2500):(32-45):(60-90):100.

[0020] Preferably, the temperature of the hydrothermal reaction in step 4 is 140-160° C., and the time of the hydrothermal reaction is 18-24 h.

[0021] Preferably, the ethanol solution in step 4 is 75% ethanol aqueous solution.

[0022] A composite adsorbent for volatile organic matter adsorption is prepared by adopting the preparation method of the composite adsorbent for volatile organic matter adsorption.

[0023] 3. Beneficial technical effects

[0024] Compared with the prior art, the present invention has the following chemical mechanisms and beneficial technical effects:

[0025] (1) In the present invention, cellulose is used as a carbon source, 2-(chloromethyl) ethylene sulfide is used to modify cellulose to obtain sulfur-containing cellulose, the sulfur-containing cellulose is treated with a porogen potassium hydroxide, carbonized in an argon atmosphere to obtain sulfur-doped porous carbon, and then the sulfur-doped porous carbon is modified by a mixed acid to obtain modified sulfur-doped porous carbon, and a large number of carboxyl groups are introduced into the sulfur-doped porous carbon. Tetrabutyl titanate is used as a titanium source, and a composite adsorbent for volatile organic compound adsorption is prepared by a hydrothermal reaction in an anhydrous ethanol solution under the action of hydrogen peroxide. During the hydrothermal reaction, the generated nano-titanium dioxide grows uniformly on the modified sulfur-doped porous carbon, effectively avoiding the agglomeration of the nano-titanium dioxide.

[0026] (2) The biomass-based porous carbon prepared in the present invention has a high specific surface area and a rich pore structure, which can expose more active adsorption sites and adsorb a large amount of volatile organic compounds. The porous carbon is modified by carboxylation, which enhances the hydrophilicity and polarity of the surface of the porous carbon material, and can form hydrogen bonds and other interaction forces with volatile organic compounds to firmly adsorb volatile organic compounds on the surface of the material, greatly improving the adsorption capacity of volatile organic compounds. At the same time, the strong adsorption capacity can also provide more reaction substrates for the photocatalytic oxidation reaction, thereby further improving the removal efficiency of volatile organic compounds. Nano-titanium dioxide, as a semiconductor photocatalyst, can generate photogenerated electrons and holes under light. These photogenerated electrons and holes have strong reducing and oxidizing properties, and can participate in the redox reaction to oxidize and decompose the organic substances adsorbed on the surface into harmless substances. The introduction of modified sulfur-doped porous carbon can improve the light absorption efficiency of the composite adsorbent, enhance the separation efficiency of photogenerated carriers, and thus improve the photocatalytic performance.

[0027] (3) When the composite adsorbent of the present invention is exposed to light, nano-titanium dioxide generates photogenerated electrons and holes, and the photogenerated electrons are captured by the sulfur-doped sites in the porous carbon material, inhibiting the rapid recombination of electrons and holes. At the same time, the active sites of sulfur-doped porous carbon may also further improve the adsorption efficiency of volatile organic compounds by forming special chemical bonds or interaction forces. Nano-titanium dioxide and modified sulfur-doped porous carbon work synergistically to further improve the removal efficiency of volatile organic compounds through adsorption and photocatalysis. The composite adsorbent is green and environmentally friendly, has low cost, and is easy to recycle to avoid secondary pollution. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] A method for preparing a composite adsorbent for adsorbing volatile organic compounds comprises the following steps:

[0031] Step 1, add cellulose and sodium hydroxide solution to reactor A, stir and mix evenly, then add 2-(chloromethyl)ethylene sulfide, wherein the mass ratio of cellulose, sodium hydroxide solution and 2-(chloromethyl)ethylene sulfide is 100:2800:155, the sodium hydroxide solution is a sodium hydroxide aqueous solution with a mass concentration of 30%, stir and mix, react at 25°C, the reaction time is 48h, after the reaction is completed, wash with acetone and deionized water, and dry at 60°C for 12h to obtain sulfur-containing cellulose;

[0032] Step 2, add sulfur-containing cellulose and potassium hydroxide in a mass ratio of 100:350 to reactor B, grind evenly, place in a tube furnace, and carbonize in an argon atmosphere. The carbonization heating rate is 2°C / min, the carbonization temperature is 650°C, and the carbonization time is 3h. After the carbonization is completed, cool, wash with dilute hydrochloric acid and deionized water to neutrality, and vacuum dry at 60°C for 12h to obtain sulfur-doped porous carbon;

[0033] Step 3: add deionized water, sulfuric acid solution and nitric acid solution to the reactor C, mix well, add sulfur-doped porous carbon, the mass ratio of deionized water, nitric acid solution, sulfuric acid solution and sulfur-doped porous carbon is 900:250:320:100, stir and react, the reaction temperature is 35°C, the reaction time is 6h, after the reaction is completed, filter, wash with deionized water, and vacuum dry at 60°C for 12h to obtain modified sulfur-doped porous carbon;

[0034] Step 4: Add ethanol solution, tetrabutyl titanate, hydrogen peroxide and modified sulfur-doped porous carbon in a mass ratio of 1800:32:60:100 into reactor D, wherein the ethanol solution is 75% ethanol aqueous solution, mix evenly, add acetic acid to adjust the pH to 3, transfer to a polytetrafluoroethylene reactor, and undergo a hydrothermal reaction. The temperature of the hydrothermal reaction is 140°C, and the time of the hydrothermal reaction is 24 hours. After the reaction is completed, filter, wash with deionized water, and vacuum dry at 60°C for 12 hours to obtain a composite adsorbent.

[0035] Example 2

[0036] A method for preparing a composite adsorbent for adsorbing volatile organic compounds comprises the following steps:

[0037] Step 1, add cellulose and sodium hydroxide solution to reactor A, stir and mix evenly, then add 2-(chloromethyl)ethylene sulfide, wherein the mass ratio of cellulose, sodium hydroxide solution and 2-(chloromethyl)ethylene sulfide is 100:300:200, the sodium hydroxide solution is a sodium hydroxide aqueous solution with a mass concentration of 30%, stir and mix, react at 30° C., the reaction time is 42 hours, after the reaction is completed, wash with acetone and deionized water, and dry at 60° C. for 12 hours to obtain sulfur-containing cellulose;

[0038] Step 2, add sulfur-containing cellulose and potassium hydroxide in a mass ratio of 100:400 to reactor B, grind evenly, place in a tube furnace, and carbonize in an argon atmosphere. The carbonization heating rate is 3°C / min, the carbonization temperature is 680°C, and the carbonization time is 2.5h. After the carbonization is completed, cool, wash with dilute hydrochloric acid and deionized water to neutrality, and vacuum dry at 60°C for 12h to obtain sulfur-doped porous carbon;

[0039] Step 3: add deionized water, sulfuric acid solution and nitric acid solution to the reactor C, mix well, add sulfur-doped porous carbon, the mass ratio of deionized water, nitric acid solution, sulfuric acid solution and sulfur-doped porous carbon is 1100:280:350:100, stir and react, the reaction temperature is 40°C, the reaction time is 5h, after the reaction is completed, filter, wash with deionized water, and vacuum dry at 60°C for 12h to obtain modified sulfur-doped porous carbon;

[0040] Step 4: Add ethanol solution, tetrabutyl titanate, hydrogen peroxide and modified sulfur-doped porous carbon in a mass ratio of 2000:36:70:100 into reactor D, wherein the ethanol solution is 75% ethanol aqueous solution, mix evenly, add acetic acid to adjust the pH to 4, and then transfer to a polytetrafluoroethylene reactor for hydrothermal reaction. The temperature of the hydrothermal reaction is 150°C and the time of the hydrothermal reaction is 20 hours. After the reaction is completed, filter, wash with deionized water, and vacuum dry at 60°C for 12 hours to obtain a composite adsorbent.

[0041] Example 3

[0042] A method for preparing a composite adsorbent for adsorbing volatile organic compounds comprises the following steps:

[0043] Step 1. Add an ethanol solution, tetrabutyl titanate, hydrogen peroxide and modified sulfur-doped porous carbon in a mass ratio of 2200:42:80:100 into reactor D, wherein the ethanol solution is a 75% ethanol aqueous solution, mix them evenly, add acetic acid to adjust the pH to 4, and then transfer them to a polytetrafluoroethylene reactor for hydrothermal reaction. The temperature of the hydrothermal reaction is 155°C and the time of the hydrothermal reaction is 22 hours. After the reaction is completed, filter, wash with deionized water, and vacuum dry at 60°C for 12 hours to obtain a composite adsorbent.

[0044] The preparation method of the modified sulfur-doped porous carbon is the same as the preparation method of the modified sulfur-doped porous carbon in Example 2.

[0045] Example 4

[0046] A method for preparing a composite adsorbent for adsorbing volatile organic compounds comprises the following steps:

[0047] Step 1, add cellulose and sodium hydroxide solution to reactor A, stir and mix evenly, then add 2-(chloromethyl)ethylene sulfide, wherein the mass ratio of cellulose, sodium hydroxide solution and 2-(chloromethyl)ethylene sulfide is 100:3200:215, the sodium hydroxide solution is a sodium hydroxide aqueous solution with a mass concentration of 30%, stir and mix, react at 35°C, the reaction time is 36h, after the reaction is completed, wash with acetone and deionized water, and dry at 60°C for 12h to obtain sulfur-containing cellulose;

[0048] Step 2, add sulfur-containing cellulose and potassium hydroxide in a mass ratio of 100:420 to reactor B, grind evenly, place in a tube furnace, and carbonize in an argon atmosphere. The carbonization heating rate is 4°C / min, the carbonization temperature is 700°C, and the carbonization time is 2h. After the carbonization is completed, cool, wash with dilute hydrochloric acid and deionized water to neutrality, and vacuum dry at 60°C for 12h to obtain sulfur-doped porous carbon;

[0049] Step 3: add deionized water, sulfuric acid solution and nitric acid solution to the reactor C, mix well, add sulfur-doped porous carbon, the mass ratio of deionized water, nitric acid solution, sulfuric acid solution and sulfur-doped porous carbon is 1200:300:380:100, stir and react, the reaction temperature is 45°C, the reaction time is 3h, after the reaction is completed, filter, wash with deionized water, and vacuum dry at 60°C for 12h to obtain modified sulfur-doped porous carbon;

[0050] Step 4: Add ethanol solution, tetrabutyl titanate, hydrogen peroxide and modified sulfur-doped porous carbon in a mass ratio of 2500:45:90:100 into reactor D, wherein the ethanol solution is 75% ethanol aqueous solution, mix evenly, add acetic acid to adjust the pH to 5, transfer to a polytetrafluoroethylene reactor, and undergo a hydrothermal reaction. The temperature of the hydrothermal reaction is 160°C, and the time of the hydrothermal reaction is 18 hours. After the reaction is completed, filter, wash with deionized water, and vacuum dry at 60°C for 12 hours to obtain a composite adsorbent.

[0051] Comparative Example 1

[0052] A method for preparing titanium dioxide for adsorbing volatile organic compounds comprises the following steps:

[0053] Step 1: add an ethanol solution, tetrabutyl titanate, and hydrogen peroxide in a mass ratio of 2200:42:80 into a reactor D, wherein the ethanol solution is a 75% ethanol aqueous solution, mix them evenly, add acetic acid to adjust the pH to 4, transfer them to a polytetrafluoroethylene reactor, and allow a hydrothermal reaction to occur. The temperature of the hydrothermal reaction is 155° C., and the time of the hydrothermal reaction is 22 hours. After the reaction is completed, filter the mixture, wash with deionized water, and vacuum dry it at 60° C. for 12 hours to obtain titanium dioxide for adsorption of volatile organic matter.

[0054] Comparative Example 2

[0055] A method for preparing a modified sulfur-doped porous carbon adsorbent comprises the following steps:

[0056] Step 1, add cellulose and sodium hydroxide solution to reactor A, stir and mix evenly, then add 2-(chloromethyl)ethylene sulfide, wherein the mass ratio of cellulose, sodium hydroxide solution and 2-(chloromethyl)ethylene sulfide is 100:300:200, the sodium hydroxide solution is a sodium hydroxide aqueous solution with a mass concentration of 30%, stir and mix, react at 30° C., the reaction time is 42 hours, after the reaction is completed, wash with acetone and deionized water, and dry at 60° C. for 12 hours to obtain sulfur-containing cellulose;

[0057] Step 2, add sulfur-containing cellulose and potassium hydroxide in a mass ratio of 100:400 to reactor B, grind evenly, place in a tube furnace, and carbonize in an argon atmosphere. The carbonization heating rate is 3°C / min, the carbonization temperature is 680°C, and the carbonization time is 2.5h. After the carbonization is completed, cool, wash with dilute hydrochloric acid and deionized water to neutrality, and vacuum dry at 60°C for 12h to obtain sulfur-doped porous carbon;

[0058] Step 3: Add deionized water, sulfuric acid solution and nitric acid solution to reactor C, mix well, add sulfur-doped porous carbon, the mass ratio of deionized water, nitric acid solution, sulfuric acid solution and sulfur-doped porous carbon is 1100:280:350:100, stir and react, the reaction temperature is 40°C, the reaction time is 5h, after the reaction is completed, filter, wash with deionized water, and vacuum dry at 60°C for 12h to obtain a modified sulfur-doped porous carbon adsorbent.

[0059] The prepared products in Examples 1-4 and Comparative Examples 1-2 were used as samples to perform corresponding tests. The test methods and test results are as follows:

[0060] The samples synthesized in Examples 1-4 and Comparative Examples 1-2 were placed in VOCs waste gas treatment devices, respectively. The main components of the VOCs waste gas included benzene, toluene, xylene and styrene. The inlet concentration of VOCs was 800 ppm. After adsorption for 6 hours, a 500W xenon lamp was used as a light source for 4 hours. The concentration of VOCs in the outlet of the mobile phase chamber was detected, and the degradation efficiency was calculated. The test results are shown in Table 1:

[0061] Table 1

[0062]

[0063] According to the test results in Table 1, the composite adsorbents prepared in Examples 1-4 have excellent ability to remove volatile organic compounds, and the degradation rate of volatile organic compounds in the sample corresponding to Example 3 can reach 99.2%. In Comparative Example 1, nano-titanium dioxide is used as a sample, and the degradation rate of volatile organic compounds is 88.8%. In Comparative Example 2, a modified sulfur-doped porous carbon adsorbent is used as a sample, and the degradation rate of volatile organic compounds is 91.5%, both of which are greatly reduced.

[0064] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A method for preparing a composite adsorbent for adsorbing volatile organic compounds, characterized in that: The steps include: Step 1, adding cellulose and sodium hydroxide solution into reactor A, stirring and mixing evenly, adding 2-(chloromethyl)ethylene sulfide, stirring and mixing, reacting, washing and drying after the reaction is completed, to obtain sulfur-containing cellulose; Step 2: Add sulfur-containing cellulose and potassium hydroxide to reactor B, grind them evenly, place them in a tube furnace, and carbonize them in an argon atmosphere. After carbonization, cool them, wash them to neutrality, and dry them to obtain sulfur-doped porous carbon. Step 3: Add deionized water, sulfuric acid solution and nitric acid solution into the reactor C, mix well, add sulfur-doped porous carbon, stir, react, filter, wash and dry after the reaction is completed to obtain modified sulfur-doped porous carbon; Step 4: add ethanol solution, tetrabutyl titanate, hydrogen peroxide and modified sulfur-doped porous carbon into reactor D, mix well, adjust pH to 3-5, transfer to a polytetrafluoroethylene reactor, undergo hydrothermal reaction, and after the reaction is completed, filter, wash and dry to obtain a composite adsorbent; In the step 1, the mass ratio of cellulose, sodium hydroxide solution and 2-(chloromethyl)ethylene sulfide is 100: (2800-3200): (155-215); The reaction temperature in step 1 is 25-35° C., and the reaction time is 36-48 h.

2. The method for preparing a composite adsorbent for adsorbing volatile organic compounds according to claim 1, characterized in that: In the step 2, the mass ratio of sulfur-containing cellulose to potassium hydroxide is 100:(350-420).

3. The method for preparing a composite adsorbent for adsorption of volatile organic compounds according to claim 1, characterized in that: In the step 2, the heating rate of carbonization is 2-4°C / min, the carbonization temperature is 650-700°C, and the carbonization time is 2-3h.

4. The method for preparing a composite adsorbent for adsorbing volatile organic compounds according to claim 1, characterized in that: In the step three, the mass ratio of deionized water, nitric acid solution, sulfuric acid solution, and sulfur-doped porous carbon is (900-1200): (250-300): (320-380):

100.

5. The method for preparing a composite adsorbent for adsorbing volatile organic compounds according to claim 1, characterized in that: The reaction temperature in step 3 is 35-45° C., and the reaction time is 3-6 h.

6. The method for preparing a composite adsorbent for adsorbing volatile organic compounds according to claim 1, characterized in that: In the step 4, the mass ratio of the ethanol solution, tetrabutyl titanate, hydrogen peroxide and modified sulfur-doped porous carbon is (1800-2500):(32-45):(60-90):

100.

7. The method for preparing a composite adsorbent for adsorbing volatile organic compounds according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step 4 is 140-160° C., and the time of the hydrothermal reaction is 18-24 hours.

8. A composite adsorbent for volatile organic compound adsorption prepared by the method for preparing a composite adsorbent for volatile organic compound adsorption as claimed in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Indoor volatile organic compound elimination agent and preparation method thereof

    CN106422719A

  • Preparation method of biomass carbon material for efficiently adsorbing volatile organic compounds

    CN108246259A

  • Thiol acrylic fiber material and synthesis method thereof

    CN102978913A

  • Hollow structure TiO2 / biomass charcoal composite material as well as preparation method and application thereof

    CN117299105A